PENGARUH LATIHAN FINDERS KEEPERS TERHADAP KECEPATAN LARI PADA ATLET ATLETIK KABUPATEN SIAK - Frederika Frentina Frederika Frentina; Ramadi Ramadi '; Ardiah Juita Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Problem identification results show that there are exercises that can have a significant influence on the running speed on the track and field athletes. The issues raised in this research is,